The Effect of setting up an Irish boarding school on the rights of Adolescence - Asror, Khozinatul; Subandi, Subandi; Jaenullah, Jaenullah; Bahri, Moh Syaiful (CV. BImbingan Belajar Assyfa, 2023)
Islamic boarding school institutions grow entirely based on religious motivation. Then, it was further developed to make efforts to broadcast and practice spiritual teachings more effective. The influence and role of Islamic boarding schools on community life are very large, including in developing youth in the community. The community hopes that the Islamic boarding school environment can influence the morals of its teenagers so that Muslim teenagers can be created morally glorious, so the role of cottage boarding school is very important to make it happen. Objective This research was conducted to describe and analyse understanding, habituation and the impact of fostering the Islamic boarding school environment on the moral behaviour of youth in SB 6 Seputih Banyak District, Lampung Regency Middle. Study This is a study field (field research) done in SB 6 Seputih Banyak Subdistrict, Central Lampung Regency is related to the impact of fostering the Islamic boarding school environment on youth morals. Researchers, in collecting the data needed as a source of information, use technique observation, interview and documentation. The data obtained, then collected and processed so that can withdraw something conclusion. Based on the results study, it can conclude that Cottage the Darul Ulum Seputih Banyak Islamic Boarding School has played a major role in developing the morals of the youth of SB 6, Seputih Banyak District, Central Lampung Regency. Activities that have been carried out regularly have been able to shape morals. The child of SB 6 Seputih has gone through much habituation. These activities also have a big impact on the development and formation of moral youth.